Greenhouse locating based on ANP-COPRAS-G methods – an empirical study based on Iran - Rezaeiniya, Nahid; Hashemkhani Zolfani, Sarfaraz; Zavadskas, Edmundas Kazimieras (International Journal of Strategic Property Management, 2012)
The selection of a location among alternative locations is a multi criteria decision-making problem including both quantitative and qualitative criteria. In this paper, we describe the research and development of hybrid MCDM methods for greenhouse locating. Selection of the most appropriate location for investor is an important problem which requires assessment and analysis of several factors. The paper clarifies the structure of important criteria in greenhouse locating. The six factors identified were: labor, government, environment, physical condition, regional economy and raw materials. In this research, analysis network process (ANP) is applied to find the relative weights among the criteria and to emphasize the interdependent relationships, thus increasing the accuracy of our results COPRAS-G method is applied to rank for five regions in Amol city, in Iran. This article can be a guideline for investors to select the best location for greenhouses. First Publish Online: 19 Jun 2012